IDENTIFIKASI PROFIL KUALITAS KOPI SEBAGAI ACUAN PENGEMBANGAN PRODUK SPESIALTI DI KAWASAN MENOREH, KULON PROGO, YOGYAKARTA - Aldicky Faizal Amri; Ervika Rahayu Novita Herawati; Rifa Nurhayati; Agus Susanto (Balai Besar Industri Hasil Perkebunan, 2020)
Abstract: An understanding the characteristics of raw materials is important for the product development process. The characteristics and methods of processing of a coffee bean will affect its final quality and the taste of its brewed coffee. In Kulon-Progo Region, the coffee quality profile has not been identified clearly. Therefore, this research was conducted to identify the quality profile of coffee that grows in the Menoreh, Kulon Progo region so that it can be used as a guideline for further product development. Identification is carried out by testing the physical, chemical, and microbiological parameters and the taste of coffee grown in the Menoreh region, Kulon Progo. Physical, chemical and microbiological parameters testing is done by referring to SNI 1-3542-2004 concerning coffee powder. Taste testing is carried out with the help of expert panelists who refer to the SCAA Cupping Protocol. Based on this research results, the quality of Menoreh coffee has met the level I quality requirements of SNI 1-3542-2004 and has the potential to be developed into specialty coffee originating from the Special Region of Yogyakarta.Keywords: Menoreh Coffee, Quality, Specialty Coffee, Product Development